Hepatitis C virus complete life cycle screen for identification of small molecules with pro- or antiviral activity - Gentzsch, Juliane; Hinkelmann, Bettina; Kaderali, Lars; Irschik, Herbert; Jansen, Rolf; Sasse, Florenz; Frank, Ronald; Pietschmann, Thomas (Antiviral research, 2011)
Infection with the hepatitis C virus represents a global public health threat given that an estimated 170 million individuals are chronically infected and thus at risk for cirrhosis and hepatocellular carcinoma. A number of direct antiviral molecules are in clinical development. However, side effects, drug resistance and viral genotype-specific differences in efficacy may limit these novel therapeutics. Therefore, a combination of well tolerated drugs with distinct mechanisms of action targeting different steps of the viral replication cycle will likely improve viral response rates and therapy success. To identify small molecules that interfere with different steps of the HCV replication cycle, we developed a novel dual reporter gene assay of the complete HCV life cycle and adapted it to 384-well high-throughput format. The system is based on a highly permissive Huh-7 cell line stably expressing a secreted luciferase. Using these cells and an efficient HCV luciferase reporter virus, perturbations of each step of the viral replication cycle as well as cell viability can be easily and quantitatively determined. The system was validated with a selected set of known HCV entry, replication and assembly inhibitors and then utilized to screen a library of small molecules derived from myxobacteria. Using this approach we identified a number of molecules that specifically inhibit HCV cell entry, or primarily virus assembly and release. Moreover, we also identified molecules that increase viral propagation. These compounds may be useful leads for development of novel HCV inhibitors and could be instrumental for the identification of as yet unknown host-derived viral resistance and dependency factors.